Multi-branched heterogeneous PEG antifouling coating enables direct biomarker detection via SPRi biosensor in clinical biofluids - Kai Su; Haiping Wu; Lu Zhang; Yuanjie Liu; Ningke Fan; Yirong Chen; Menghan Li; Jianxiong Liu; Yutao Wang; Yurong Yan (Chemical Engineering Journal, 2026)

Spatiotemporal variations and topographic modulation of black carbon in the Sichuan-Chongqing Region, China - Yurong Zhang; Yong Han; Yan Liu (Atmospheric Environment, 2026)

Effects of dietary γ-aminobutyric acid supplementation on growth, feed intake, and intestinal health of the juvenile Chinese mitten crab (Eriocheir sinensis) fed with high plant protein diets - Longhui Liu; Xuming Lu; Kejing Huang; Guiyuan Li; Yurong Liu; Yuxi Yan; Erchao Li; Liqiao Chen; Xiaodan Wang (Aquaculture International, 2026)

Corrigendum to: “Benzo[a]pyrene exposure promotes RIP1-mediated necroptotic death of osteocytes and the JNK/IL-18 pathway activation via generation of reactive oxygen species” [Toxicology, 476, June 2022, 153244] - Tao Zhang; Yuchen Shen; Ruirong Zhu; Weiyan Shan; Yurong Li; Ming Yan; Yun Zhang (Toxicology, 2026)

Amorphous PdSe ultrafine nanoparticles boosts ethanol electrooxidation via dual-pathway mechanism - Zhihan Liu; Shiguo Yan; Qin Luo; Yifan Cao; Yurong Fu; Huanyue Zhang; Yiyang Wang; Xiaodi Tang; Yong Yi; Cuilan Tang (Chemical Engineering Journal, 2026)

Elucidation of the fungal community composition and quality of medium-high temperature Daqu: A study based on second-generation sequencing and electronic sensor technologies - Yurong WANG; Yan Lei; Qiangchuan Hou; Bangkun Wang; Minwan Liu; Zhuang Guo (Food and Bioproducts Processing, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Molecular mechanisms and genic resources responsive to salinity stress and their applications in maize and other crop breeding - Yingwei Qu; Juan Zhang; Yuqian Zhang; Yurong Xie; Xiaocong Cao; Jianing Li; Zhihong Yin; Jie Luo; Yan Long; Pervez H. Zaidi; Xiangyuan Wan (Science Bulletin, 2026)

Boron-doped diamond electrodes for environmental applications: From structure-property relationships to electrochemical remediation and sensing - Liwei Chen; Yurong Guo; Yanrong Chen; Yan Zhang; Mingming Gao; Yingying Jing; Yen Leng Pak; Xing Gao; Suqin Han; Lan Bao; Jibin Song (Journal of Environmental Chemical Engineering, 2026)

In-Depth Water Quality Analysis in Fengle Reservoir, China - Ran Chen; Jiamin Chai; Zhixu Kang; Yan Li; Lili Dong; Liping Qian; Yurong Wei; Xintong Li; Qidi Liu; Yixin Ma; Jun Cui; Shunli Wan; et al. (Water Conservation Science and Engineering, 2026)

Identify and Suppress Magnetotelluric Data using Long Short-Term Memory, Multi-Head Attention and ResNet - Yi Tang; Tianjun Cheng; Lei Zhou; Xingbing Xie; Yurong Mao; Liangjun Yan (Pure and Applied Geophysics, 2026)

Soil Fungi Composition and Functional Groups in Phosphate Mine Spontaneous Recovery Areas: A Combined High‐Throughput and Traditional Approaches - Yongsheng Peng; ChengJiao Dao; YuRong Wang; Rong Tang; Neelamanie Yapa; Garumuni Dilrukshi Nadeeshani Menike; Anuruddha Karunarathna; Abdallah M. Elgorban; Alanoud T. Alfagham; Saowaluck Tibpromma; Y. A. P. K. Dayasena; Kai Yan (New Zealand Journal of Botany, 2026)
Our study on the composition and functional groups of soil fungi in phosphate mine spontaneous recovery areas has identified several fungal genera that play a crucial role in soil regeneration. This finding carries significant practical implications for the methodologies employed in mine site reclamation. We used amplicon sequencing‐based high‐throughput sequencing (HTS) and traditional fungal culturing methods in the Kunyang phosphate mining area of Kunming City, Yunnan Province, China, to comprehensively assess fungal community composition and functional diversity during spontaneous regeneration. The fungal communities in the natural recovery area differ significantly from those in the abandoned mining area, exhibiting notably higher fungal diversity indices and a more complex co‐occurrence pattern. Through HTS, 13 fungal phyla and 447 fungal genera were identified. Among them, Ascomycota is the dominant phylum, followed by Basidiomycota , and Mortierella was the primary genus. All cultured fungi belong to Ascomycota , comprising 16 genera, among which Purpureocillium and Penicillium are predominant. The majority of cultured fungi belong to pathogenic and saprophytic groups, while Mortierella is the only potential symbiotic genus. Notably, six fungal genera were identified exclusively through culturable approaches: Aureobasidium , Cladosporium , Cytospora , Discohainesia , Neopyrenochaeta , and Saccharomyces . These genera play a crucial role in soil regeneration, and their identification is a significant step toward understanding their functional characteristics. The results indicate that rhizosphere fungal communities vary significantly under distinct restoration strategies. This underscores the importance of considering regional specificity, such as local climate and soil conditions, when harnessing fungi for vegetation rehabilitation. The synergistic application of high‐throughput sequencing alongside culturable methods is not only beneficial but also crucial for the efficient screening and utilization of functional fungi. This integration reassures professionals in the field about the effectiveness and reliability of their research methods, thereby enhancing their confidence in the outcomes.

Physicochemical properties and fine structural characterization of starch during wheat milling: A comparison of milling methods - Yurong Zhou; Jing Zhang; Chao Chen; Yijun Yao; Wenfei Xiong; Donglei Jiang; Yan Ma; Na Zhang; Lifeng Wang (Carbohydrate Polymers, 2026)

Coupling toxicokinetics and toxicodynamics of organ-specific antioxidant responses to sulfamethoxazole in Sinonovacula constricta: an integrated biomarker response assessment - Yurong Zhang; Fuxi Nie; Qingxi Han; Guoquan Wang; Zhongyong Yan; Zhen Mao; Rijin Jiang; Haifeng Jiao (Marine Environmental Research, 2026)

Simple methods for imperfection sensitivity analysis of caisson skirts under suction installation - Ruizhe Xu; Yurong Zhang; Dengfeng Fu; Yue Yan; Wentao Cui; Shuntao Fan; Dong Wang (Computers and Geotechnics, 2026)

Enhanced OH− transport and storage in oxygen vacancy-enriched α-Ga2O3 shells constructed on GaN nanowires for supercapacitor - Junjie Jiang; Ronghuo Yuan; Zhiquan Lang; Huayu Ji; Zhimin Zou; Chunhai Jiang; Yurong Wu; Kun Wu; Yuhui Zhang; Ningbo Liao; Guang-Ling Song; Min-Ming Jiang; et al. (Chemical Engineering Journal, 2026)

Decolorization of malachite green by free and immobilized Pseudomonas sp. strain C2-4 - Yue Xiao; Yichao Zhao; Yurong Yan; Jinyan Liu; Ruiling Lyu; Yongliang Zheng; Xia Fan (World Journal of Microbiology and Biotechnology, 2026)

MLL1-pioneered H3K4me3 modification on KLF7 promoter accelerates the invasion of fibroblast-like synoviocytes in rheumatoid arthritis - Yurong Cen; Chunhua Yan; Chunmei Qian; Qin Wang (In Vitro Cellular & Developmental Biology - Animal, 2026)

Point discharge molecular emission spectrometer as a highly sensitive GC detector for the analysis of furans in food products - Yuan Yang; Xiaoli Wu; Qiuyi Yan; Hongling Zhou; Yurong Deng; Chengbin Zheng (Food Chemistry, 2025)

Antigelation spinning method to fabricate liquid crystal elastomer fibers with high orientation and reliable actuation for biomimetic devices - Xulian Hu; Chuhao Ma; Jiazhao Tan; Shaoji Wu; Caihong Gong; Wanjiang Li; Zhiming Qiu; Yurong Yan (Chemical Engineering Journal, 2025)

Differential characterization of medium-temperature Daqu from different geographical regions: bacterial profile, color, taste, and flavor - Yurong Wang; Yan Lei; Jianhui Zhang; Qiangchuan Hou; Zhuang Guo (World Journal of Microbiology and Biotechnology, 2025)

Investigating structural-functional brain covariation in bipolar disorder using a multimodal fusion approach - Wei Zhang; Yingling Hou; Xinyi Wang; Yurong Sun; Junneng Shao; Rui Yan; Xuejun Kang; Zhijian Yao; Qing Lu (Brain Imaging and Behavior, 2025)

Ginsenoside Rg1 alleviated arsenic-induced liver fibrosis through modulating gut microbiome - Ye Li; Yurong Ren; Ning Jia; Xiaoming Zhang; Yuanqing Luo; Jianrong Cao; Yan Yuan; Zitian Wang; Yiting Gong; Xueyuan Zhi (Food Bioscience, 2025)

Wind-blown litter transports more carbon and nutrients than wind-blown dust in semi-arid steppes - Yuhong Luo; Yurong Cai; Na Zhu; Le Li; Nuo Xu; Yufan Bao; Yuchun Yan (Plant and Soil, 2025)

The Central Role of NRF2 in Cancer Metabolism and Redox Signaling: Novel Insights into Crosstalk with ER Stress and Therapeutic Modulation - Amie N. Joof; Ousman Bajinka; Yan Zhou; Fangyuan Ren; Yurong Tan (Cell Biochemistry and Biophysics, 2025)

Interaction influence characteristics of air quality and aerosol properties between Beijing-Tianjing-Hebei (BTH) and Yangtze River Delta (YRD), China - Guopan Chen; Yong Han; Xin Wang; Yurong Zhang; Yan Liu; Li Dong; Qicheng Zhou; Peng Xiao (Urban Climate, 2025)

A portable photoelectrochemical aptasensor based on voltage−resolved dual−signal output for the determination of chloramphenicol - Qiao Zhang; Yue Sun; Lei Yu; Xing Gao; Yan Huang; Xiao Sun; Yen Leng Pak; Yurong Guo; Yan Sun; Zhao Wang; Jibin Song (Journal of Hazardous Materials, 2025)

Passivation mechanism driven selective leaching for recycling spent LiFePO4 lithium-ion batteries - Yurong Han; Menglong Yan; Yinzhuang Fang; Yifeng Han; Yi Chen; Liangyou Lin; Jingwen Qian; Tao Mei; Xianbao Wang (Journal of Environmental Chemical Engineering, 2025)

Black carbon in major global source areas from 2000 to 2023: Spatiotemporal variation, vertical distribution, and extreme case analysis - Yurong Zhang; Yong Han; Yan Liu; Ximing Deng; Tianwei Lu; Qicheng Zhou; Li Dong (Environmental Pollution, 2025)

A critical review of biochar for the remediation of PFAS-contaminated soil and water - Dezhan Liang; Caibin Li; Hanbo Chen; Erlend Sørmo; Gerard Cornelissen; Yurong Gao; Febelyn Reguyal; Ajit Sarmah; Jim Ippolito; Claudia Kammann; Fangbai Li; Yerbolat Sailaukhanuly; et al. (Science of The Total Environment, 2024)

Structurally programmed bioderived polyimide for foldable humidity sensors with ultrafast response and recovery times - Caihong Gong; Huilong Liu; Shaoji Wu; Zhao Liu; Sutong Zheng; Yanhuang Tang; Zhiming Qiu; Rui Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

A cost-saving, safe, and highly efficient natural mediator for laccase application on aflatoxin detoxification - Shenglong Liu; Yu Zhou; Yan Feng; Qixia Peng; Yurong Li; Cheng He; Zemin Fang; Yazhong Xiao; Wei Fang (Food Chemistry, 2024)

Automatic identification of cirques based on RetinaNet model and pseudo-color image fusion method - Zhenxin Shi; Guiquan Mo; Yurong Cui; Libo Yan; Yunshan Lu; Lina Hou; Lansong Lv; Huixuan Li (Advances in Space Research, 2024)

Spatiotemporal changes of urban heat island effect relative to land surface temperature: a case study of Jinan City, China - Guiquan Mo; Libo Yan; Zhiyong Li; Zongyao Wang; Sixuan Chen; Huixuan Li; Shuwei Zheng; Yurong Cui (Environmental Science and Pollution Research, 2024)

Split activator of CRISPR/Cas12a for direct and sensitive detection of microRNA - Wen He; Xinyu Li; Xinmin Li; Minghui Guo; Mengxuan Zhang; Ruiwei Hu; Menghan Li; Shijia Ding; Yurong Yan (Analytica Chimica Acta, 2024)

Elucidating the physicochemical parameters, bacterial community structure, and correlation characteristics of medium-high temperature Daqu - Yan Lei; Wenchao Cai; Yurong Wang; Bangkun Wang; Minwan Liu; Chunhui Shan; Zhuang Guo (Food Bioscience, 2024)

A novel electrochemiluminescent cytosensor using 3D multivalent aptamer recognition and covalent organic frameworks-associated DNA walker for highly efficient capture and detection of rare CTCs - Minghui Guo; Bo Shen; Wen He; Xinyu Li; Xinmin Li; Menghan Li; Ruiwei Hu; Mengxuan Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

An all-in-one enzymatic DNA network based on catalytic hairpin assembly for label-free and highly sensitive detection of APE1 - Shaoying Zhou; Xingrong Li; Xiaojia Shu; Xiaoying Cai; Haiping Wu; Shijia Ding; Yurong Yan (Analytica Chimica Acta, 2023)

Branched DNA switchable CRISPR-Cas12a system for sensing FEN1 activity - Xingrong Li; Decai Zhang; Xiaoying Cai; Xiaojia Shu; Zijie Zeng; Shijia Ding; Yurong Yan (Chemical Engineering Journal, 2023)

Integrative transcriptome and metabolome revealed the molecular mechanism of Bacillus megaterium BT22-mediated growth promotion in Arabidopsis thaliana - Xiao Liu; Yan Du; Xiaofan Na; Man Wang; Ying Qu; Linghui Ge; Yuanmeng Wang; Linqi Gao; Wenke Bai; Yurong Bi; Libin Zhou (Journal of Plant Physiology, 2023)

Levilactobacillus yiduensis sp. nov., Isolated from Zha-chili in Yidu County, Hubei Province, China - Yun Dong; Yurong Wang; Huijun Zhao; Yan Zhang; Haibo Zhang; Yafang Sun; Zhuang Guo (Current Microbiology, 2023)

A highly selective red-emitting fluorescent probe and its micro-nano-assembly for imaging endogenous peroxynitrite (ONOO−) in living cells - Jingran Zhang; Lele Liu; Yanan Wang; Chao Wang; Yurong Guo; Zihan Yuan; Yan Jia; Peng Li; Shuqing Sun; Guangjiu Zhao (Analytica Chimica Acta, 2023)

Micron SiOx encapsulated into amorphous B, N Co-doped carbon nanotube network for high-capacity and long-durable Li-ion half/full batteries - Bingxin Shen; Ning Fu; Yuwen Chen; Wei Shao; Yurong Yan; Jia Huang; Zhenglong Yang (Chemical Engineering Journal, 2023)

A new process to further remove dissolved organic matter and disinfection by-product formation potential during drinking water treatment - Chongtian Lei; Yurong Chen; Aimin Li; Rui Gao; Ziang Zhang; Junxia Chen; Peng Shi; Qing Zhou; Yan Ma (Environmental Science and Pollution Research, 2022)

Interpreting the nonstationary relationship between El Niño–Southern Oscillation and the winter precipitation over southeast China - Wenqian Tang; Xin Geng; Yan Zhao; Yurong Gao; Yiwan Huang; Shuchang Ning (International Journal of Climatology, 2022)
The amount of winter precipitation over southeast China (SCWP) is significantly affected by the El Niño–Southern Oscillation (ENSO), with generally an enhanced SCWP response to El Niño events. In this paper, we find that this relationship shows remarkable nonstationarities on the multidecadal timescale. Running ENSO–SCWP correlation maintains statistically significant before the mid‐1960s and after the mid‐1990s but not during the interim period, which exhibits an approximate synchronized temporal evolution with the Atlantic Multidecadal Oscillation (AMO). A statistical method for interpreting nonstationary relationships is then applied to quantitatively verify and measure this possible AMO modulation. It is demonstrated that the nonstationary ENSO–SCWP correlation can be expressed to a large extent by the influence of the AMO–ENSO nonlinear effect (AMO*Niño3.4) on the SCWP. This influence intensifies the ENSO–SCWP relationship during the positive AMO phase but weakens it during the negative AMO phase. Therefore, the nonstationarity in the ENSO–SCWP relationship comes predominantly from an AMO modulation via this key nonlinear effect. We further suggest that a positive AMO favours a westward shift of ENSO sea surface temperature (SST) anomaly pattern in the tropical Pacific. Correspondingly, the anomalous western North Pacific (WNP) anticyclone also migrates westward, which gives rise to pronounced moisture transports and vertical motions over the adjacent southeast China, thereby resulting in a significant ENSO–SCWP relationship. In contrast, during the negative AMO phase, the eastward‐shifted ENSO SST and WNP anticyclonic anomalies produce significant atmospheric anomalies primarily to the east of the Chinese mainland, thus having less effect on the SCWP.

Rapid and specific detection of Fusarium acuminatum and Fusarium solani associated with root rot on Astragalus membranaceus using loop-mediated isothermal amplification (LAMP) - Yan Wang; Chunwei Wang; Yurong Ma; Xiqian Zhang; Hongbin Yang; Guangxin Li; Xinfeng Li; Meiqin Wang; Xiaojun Zhao; Jianming Wang; Xianhong Zhang (European Journal of Plant Pathology, 2022)

The fertile island effect collapses under extreme overgrazing: evidence from a shrub-encroached grassland - Yurong Cai; Yuchun Yan; Dawei Xu; Xingliang Xu; Chu Wang; Xu Wang; Jinqiang Chen; Xiaoping Xin; David J Eldridge (Plant and Soil, 2020)

Nitric oxide and hydrogen peroxide increase glucose-6-phosphate dehydrogenase activities and expression upon drought stress in soybean roots - Xiaomin Wang; Mengjiao Ruan; Qi Wan; Wenliang He; Lei Yang; Xinyuan Liu; Li He; Lili Yan; Yurong Bi (Plant Cell Reports, 2020)

Shrub patches capture tumble plants: potential evidence for a self-reinforcing pattern in a semiarid shrub encroached grassland - Yuchun Yan; Dawei Xu; Xingliang Xu; Deli Wang; Xu Wang; Yurong Cai; Jinqiang Chen; Xiaoping Xin; David J Eldridge (Plant and Soil, 2019)

An experimental study on metal precipitation driven by fluid mixing: implications for genesis of carbonate-hosted lead–zinc ore deposits - Yan Zhang; Runsheng Han; Xing Ding; Junjie He; Yurong Wang (Acta Geochimica, 2019)

Adiponectin Suppresses T Helper 17 Cell Differentiation and Limits Autoimmune CNS Inflammation via the SIRT1/PPARγ/RORγt Pathway - Kai Zhang; Yawei Guo; Zhenzhen Ge; Zhihui Zhang; Yurong Da; Wen Li; Zimu Zhang; Zhenyi Xue; Yan Li; Yinghui Ren; Long Jia; Koon-Ho Chan; et al. (Molecular Neurobiology, 2017)

Arctigenin Suppress Th17 Cells and Ameliorates Experimental Autoimmune Encephalomyelitis Through AMPK and PPAR-γ/ROR-γt Signaling - Wen Li; Zhihui Zhang; Kai Zhang; Zhenyi Xue; Yan Li; Zimu Zhang; Lijuan Zhang; Chao Gu; Qi Zhang; Junwei Hao; Yurong Da; Zhi Yao; et al. (Molecular Neurobiology, 2016)

Assessment of arbuscular mycorrhizal fungi status and heavy metal accumulation characteristics of tree species in a lead–zinc mine area: potential applications for phytoremediation - Yurong Yang; Yan Liang; Amit Ghosh; Yingying Song; Hui Chen; Ming Tang (Environmental Science and Pollution Research, 2015)

ZSTK474, a novel PI3K inhibitor, modulates human CD14+ monocyte-derived dendritic cell functions and suppresses experimental autoimmune encephalomyelitis - Zhenyi Xue; Wen Li; Huafeng Wang; Biao Huang; Zhenzhen Ge; Chao Gu; Ying Liu; Kai Zhang; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; et al. (Journal of Molecular Medicine, 2014)

Immunogenicity of the capsid precursor and a nine-amino-acid site-directed mutant of the 3C protease of foot-and-mouth disease virus coexpressed by a recombinant goatpox virus - Wenge Ma; Jie Wei; Yurong Wei; Huiling Guo; Yinghong Jin; Ying Xue; Yan Wang; Zhong Yi; Liya Liu; Jiong Huang; Lijian Wang (Archives of Virology, 2014)

Embelin Suppresses Dendritic Cell Functions and Limits Autoimmune Encephalomyelitis Through the TGF-β/β-catenin and STAT3 Signaling Pathways - Zhenyi Xue; Zhenzhen Ge; Kai Zhang; Rui Sun; Juhong Yang; Rong Han; Meiyu Peng; Yan Li; Wen Li; Da Zhang; Junwei Hao; Yurong Da; et al. (Molecular Neurobiology, 2014)

Quantifying and analyzing neighborhood configuration characteristics to cellular automata for land use simulation considering data source error - Hao Wu; Lu Zhou; Xu Chi; Yan Li; Yurong Sun (Earth Science Informatics, 2012)